Sistem Pakar Dalam Diagnosa Penyakit Pada Tanaman - Mulyadi; Dyan Wahyuni (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
Diseases and pests cannot be distinguished from the secondary crops that farmers encounter. To overcome this. Farmers have to rely on improvised expertise and information from others, which is ineffective due to the scarcity of experts in secondary crops. An expert system is a solution to the limitations of an expert in his profession. The forward chaining method is used in this expert system and website-based applications. Users who need information or counseling about diseases and pests that affect secondary crops can access this expert system online. The expert system will diagnose signs to which application users will respond and will produce conclusions and treatments for diseases and pests that affect secondary crops. Furthermore, the decline in the level of crop production, especially for secondary crops, is caused by disease attacks. In addition, the delay in handling due to the lack of experts also affects the decrease in the level of crop production. So we need an expert system in decision making. The results of this study can be used as a tool to identify 42 types of diseases in palawija plants and their solutions with input in the form of symptoms of damage that are visible on the outside of the plant. The results in the form of research can also display pictures of the disease, the name of the disease, its symptoms, and solutions that can be seen by the user to overcome the disease. Users can also print the diagnostic results by pressing the print button to see the results of the solution for the disease.